Plan de gestión en educación ambiental para empresas Polar - Santos, Mariana; Pellegrini, Nila; Reyes, Rosa (Tierra Infinita, 2015)
The work arises from the need to disseminate knowledge on environmental issues and starts mitigate, prevent and solve problems associated production processes that impact on sustainable development. The aim is to develop a tool that can be used by Empresas Polar for implementation of training programs for their workers. A diagnosis will be developed to identify, describe, analyze and evaluate the situation in which the company is located in relation to environmental education; needs that the company has identified; objectives were defined for the implementation of the management plan and management plan that contains the programs, projects and activities are structured. Environmental education plan focused on workers operating areas in plants, using as main strategy empowerment, so make them share in best environmental practices are developed